Adolescent mice show anxiety- and aggressive-like behavior and the reduction of long-term potentiation in mossy fiber-CA3 synapses after neonatal maternal separation. (1st March 2016) - Shin, S.Y.; Han, S.H.; Woo, R.-S.; Jang, S.H.; Min, S.S.
Highlights: Maternal separation induced anxiety and aggressive-like behavior during adolescence. LTP in the MF-CA3 synapse was reduced in the maternal separation group. PPF ratios in the MF-CA3 synapse were increased in the maternal separation group. An increased anxiety and aggression by early life stress may be associated with synaptic plasticity at MF-CA3 synapse. Abstract: Exposure to maternal separation (MS) during early life is an identified risk factor for emotional disorders such as anxiety and depression later in life. This study investigated the effects of neonatal MS on the behavior and long-term potentiation (LTP) as well as basic synaptic transmission at hippocampal CA3-CA1 and mossy fiber (MF)-CA3 synapses in adolescent mice for 19 days. When mice were adolescents, we measured depression, learning, memory, anxious and aggressive behavior using the forced swimming test (FST), Y-maze, Morris water maze (MWM), elevated plus maze (EPM), three consecutive days of the open field test, the social interaction test, the tube-dominance test and the resident–intruder test. The results showed that there was no difference in FST, Y-maze, and MWM performance. However, MS mice showed more anxiety-like behavior in the EPM test and aggressive-like behavior in the tube-dominance and resident–intruder tests. In addition, the magnitude of LTP and release probability in the MF-CA3 synapses was reduced in the MS group but not in the CA3-CA1 synapse. Our results indicate that early life stress due to MS may induce anxiety- and aggressive-like behavior during adolescence, and these effects are associated with synaptic plasticity at the hippocampal MF-CA3 synapses.